Evidence-based association work: The extended code of ethics of the “Verein für Socialpolitik” - Alexander Kriwoluzky; Aderonke Osikominu; Doris Weichselbaumer; Georg Weizsäcker (Wirtschaftsdienst)
Abstract The new Code of Ethics of the Verein für Socialpolitik takes a stand against discrimination against women and minorities, sexual and other harassment in the workplace and the creation of a hostile environment. Recent research shows that equality for women and minorities in economics has not yet been achieved. The expanded Code of Ethics is a step towards greater equal opportunity.